BTBD9 and dopaminergic dysfunction in the pathogenesis of Restless Legs Syndrome - Lyu, Shangru (Brain Struct Funct, 2020)
Restless Legs Syndrome (RLS) is characterized by an urge to move the legs, usually accompanied by uncomfortable sensations. RLS symptoms generally happen at night and can be relieved by movements. Genetic studies have linked polymorphisms in BTBD9 to a higher risk of RLS. Knockout of BTBD9 homolog in mice (Btbd9) and fly results in RLS-like phenotypes. A dysfunctional dopaminergic system is associated with RLS. However, the function of BTBD9 in the dopaminergic system and RLS is not clear. Here, we made use of the simple Caenorhabditis elegans nervous system. Loss of hpo-9, the worm homolog of BTBD9, resulted in hyperactive egg-laying behavior. Analysis of genetic interactions between hpo-9 and genes for dopamine receptors (dop-1, dop-3) indicated that hpo-9 and dop-1 worked similarly. Reporter assays of dop-1 and dop-3 revealed that hpo-9 knockout led to a significant increase of DOP-3 expression. This appears to be evolutionarily conserved in mice with an increased D(2) receptor (D(2)R) mRNA in the striatum of the Btbd9 knockout mice. Furthermore, the striatal D(2)R protein was significantly decreased and the dynamin I was increased. Overall, activities of DA neurons in the substantia nigra were not altered, but the peripheral D(1)R pathway was potentiated in the Btbd9 knockout mice. Finally, we generated and characterized dopamine neuron-specific Btbd9 knockout mice and detected active-phase sleepiness, suggesting that dopamine neuron-specific loss of Btbd9 is sufficient to disturb the sleep. Our results suggest that increased activities in the D(1)R pathway, decreased activities in the D(2)R pathway, or both may contribute to RLS.